Prevalence of Plasmodium falciparum Malaria among Pregnant Students in Dodoma Region, Tanzania: No Cases Have Been Detected - Zablon, Karen N. (Malar Res Treat, 2015)
Malaria in pregnancy, being often asymptomatic, is a major problem in endemic African countries. It is characterized by anemia and placental malaria leading to poor pregnancy outcomes. In 2001 Tanzania adopted an intermittent-preventive treatment of malaria in pregnancy (IPTp) policy, which recommends receiving doses of antimalarial drugs every planned visit to the antenatal care centre (ANC), starting from the second trimester. Currently the policy is valid across the whole country, regardless that there are regions with very low malaria endemicity in Tanzania, such as Dodoma region. The current study aimed to show the real prevalence of malaria among young pregnant women in Dodoma region, by measuring the prevalence of malaria among University of Dodoma (UDOM) students, and to describe the social health care features of student female community. Two methods of malaria diagnostic, microscopy, and rapid test, as well as retrospective inspection of ANC registry book, showed the very low prevalence of malaria disease among pregnant students, approximately 0.3%. Additionally, the sociodemographic data from the questionnaires showed that all students use different malaria preventive measures, and most of them have the regular sexual partner. This fact approves the correlation between illiteracy of woman and the risk of malaria infection transmission.